THE ANALYSIS OF COCOA FERMENTATION WITH THE ADDITION OF YEAST AND LACTIC ACID BACTERIA - Analianasari Analianasari; M. Perdiansyah Mulia Harahap Hutasuhut; Deary Amethy Zahrotinufus Joen (Jurnal Pengembangan Agroindustri Terapan, 2023)
Abstract One of the factors that affect the quality of cocoa beans is post-harvest handling such as the fermentation process. Fermentation plays an important role in determining the final quality of dried cocoa beans. Chocolate flavors can be produced from microbial fermentation from high-quality cocoa bean raw materials by utilizing microbes. This study aims to calculate the number of microbes at the beginning and end of the cocoa bean fermentation process, observing the pH value, temperature, and color of cocoa beans. The treatment carried out is a fermentation variation consisting of: (1) natural fermentation or without the addition of microorganisms; (2) controlled fermentation with the addition of microorganisms consisting of Saccharomyces cerevisiae, Lactic Acid Bacteria simultaneously added at the beginning of fermentation. The addition of microorganisms is 106 CFU / 1kg of cocoa beans each. Fermentation is carried out in a fermentation box with a capacity of 1 kg of fresh cocoa, at room temperature (33-35oC), for 4 days. The analysis carried out includes calculating the number of microbes at the beginning and end of fermentation, measuring pH, and organoleptic observations of the color of fermented cocoa beans. The results of the experiment can be concluded that there is an increase in the addition of mixed inoculum (Saccharomyces cerevisiae and Lactobacillus lactis) affecting the influence of chemical changes of the substrate during fermentation; the temperature value in cocoa fermentation ranges from 30 – 32 oC, the pH value in cocoa fermentation does not have a significant increase; and the color of cocoa beans from mixed inoculum fermentation is close to good with a dominant brown color against purple